Effectiveness of Precision-guided Munitions on Armour Systems - Gupta, Rajiv; Dayal, Arun; Sharma, Ichchha Shankar (Defense science journal, 2007)
Simulation methodology has been used to analyse the effectiveness of multi-barrel rocketlauncher system (MBRLs) delivering precision-guided munitions (PGMs) on armour forcedeployed in concentration areas under various terrain conditions. The methodology considersvarious aiming strategies, the effectiveness of the sensor and the imprecision in informationavailable about the target to evaluate the effectiveness of the MBRL system.